YOU ARE FINISHED WITH IT.

- H(x) = (2x+1)
^{3} - J(x) = 2x
^{3}+ 1 - K(x) = sqrt(6x-5)
- L(x) = sin(7x
^{2}-4)

**Solutions.** We can build the functions H and J from these two simpler functions.

With these simpler functions, we find that

H(x) = g(f(x)): (first multiply by two and add one, then cube) andIn order to decompose K, we note that when K is applied to a real number x, it first multiplies x by 6 and subtracts 5; the last (or outermost) step is to take the square root. We therefore take m to be the linear function given by m(x)=6x-5. We find thatJ(x) = f(g(x)): (first cube, then multiply by two and add one).

In order to decompose L, we form the quadratic function